2019
DOI: 10.1016/j.amsu.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The role of pectoral nerve blocks in a day-case mastectomy service: A prospective cohort study

Abstract: BackgroundIt is now recognised that the majority of breast surgery can be safely undertaken as day case procedures. We aimed to evaluate the effect of pectoral nerve (Pecs2) blocks on recovery parameters and day case rates in patients undergoing mastectomy for breast cancer.MethodsA prospective cohort study was performed in a single NHS Foundation trust between 1st April 2014 and 31st December 2016. Visual analogue scale (VAS) pain scores (0–10) at 4 and 8 h, episodes of post-operative nausea ± vomiting (PONV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In terms of non-level-1 evidence studies, several cohort studies demonstrated the efficacy of PECS II in reducing post-operative pain and opioid consumption compared to both controls (general anesthesia only), and serratus anterior plane blocks. 56 58 Several case reports show that PECS II provided sufficient analgesia without GA in patients undergoing breast conserving surgery. 59 , 60 However, the evidence for using PECS II without GA is sparse and should only be considered as a last resort option.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of non-level-1 evidence studies, several cohort studies demonstrated the efficacy of PECS II in reducing post-operative pain and opioid consumption compared to both controls (general anesthesia only), and serratus anterior plane blocks. 56 58 Several case reports show that PECS II provided sufficient analgesia without GA in patients undergoing breast conserving surgery. 59 , 60 However, the evidence for using PECS II without GA is sparse and should only be considered as a last resort option.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our study differ slightly from some recently published evidence showing the efficacy of PECS block on reducing perioperative opioid use in subjects undergoing breast surgery. The vast majority of prospective and retrospective studies, systematic reviews, and meta-analysis published in recent years have shown that the combination of general anesthesia and PECS blocks reduces the severity of postoperative pain and perioperative opioid consumption, and positively impact other postoperative outcomes such as PONV and the length of hospital stay when compared to MMA strategies without loco-regional anesthesia techniques ( 16 19 , 21 26 , 30 , 31 , 41 45 ). Therefore, the addition of PECS blocks to general anesthesia may provide adequate postoperative analgesia and substantially reduce perioperative opioid consumption ( 17 , 18 , 24 , 27 , 30 , 42 , 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that opioid consumption in our study was comparable between groups most likely did not allow for a significant inter-group difference in PONV. Several clinical studies and meta-analysis showing a significant impact of PECS blocks on opioid consumption have reported a marked reduction in PONV frequency when compared with control groups or with MMA regimens without peripheral nerve block ( 19 , 26 , 28 , 30 , 31 , 45 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study by Chiu et al clearly showed a drastic reduction in PONV occurrence after the initiation of ERAS pathways for total mastectomy compared with a non-ERAS cohort (28% vs. 50%, respectively; p<0.001) (107). The use of regional nerve blocks (e.g., pectoral blocks or PECS, paravertebral, erector spinae plane block, and interfascial plane block) as a central component of multimodal opioid-free perioperative analgesia has had a significant impact on the frequency of PONV after breast surgery (110)(111)(112)(113)(114).…”
Section: Anesthetic Management and Postoperative Nausea And Vomiting ...mentioning
confidence: 99%